Reacting in time to qualification needs: Towards a cooperative implementation? - Sophie Rouault; Heidi Oschmiansky; Isabelle Schömann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Upgrading the qualification level of the workforce has become a central issue among the governments of the European Union : in the race towards global economic competitiveness, human capital development should play a key role. Taking this statement as point of departure, the contributions gathered here explore how the qualification needs of firms and workers - once identified - are answered. The common focus lies in analysing the co-ordination schemes established among labour market actors the national, regional and supranational levels to implement and institutionalize new labour market arrangements for a more effective qualification matching. – – Die Erhöhung des Qualifikationsniveaus der Arbeitskräfte ist ein zentrales Anliegen der Regierungen der Europäischen Union: im globalen ökonomischen Wettbewerb spielt die Entwicklung des Humankapitals eine zentrale Rolle. Diesem Ausgangspunkt entsprechend untersuchen die Beiträge des Bandes, wie der identifizierte Qualifizierungsbedarf von Unternehmen und Beschäftigten gedeckt werden kann. Der gemeinsame Fokus besteht in der Analyse der Koordinierungsmustern der Akteuren der nationalen, regionalen und supranationalen Ebene für die Implementation und Institutionalisierung neuer Arbeitsmarktarrangements, um ein effektiveres Qualifizierungs-Matching zu gewährleisten.
Additional information: Proceedings of a conference organised by the WZB on the 27 - 28 September 2001, within the research network FreQuenz supported by the Federal Ministry for Training and Research (BMBF)
Keywords: 330; Berufsbildungspolitik; Arbeitsmarktpolitik; Public-Private Partnership; Job Enlargement; Beschäftigungsgesellschaft; Sozialpartner; EU-Staaten